Prisons in America - McShane, Marilyn D. (LFB Scholarly Publ., 2008)
Punishment and rehabilitation -- A history of incarceration in the United States -- Prison leasing, prison industry and the work ethic -- The corrections system today -- Prison management and the role of the correctional officer -- Classification and programming -- Prisonization, rules and discipline -- Prison violence -- Issues in medical care -- Legal issues in corrections -- Recreation, privileges, visitation and family relations -- Overcrowding, new construction and privatization